Whole Education: An Approach from Research - Díaz Monsalve, Ana Elsy; Quiroz Posada, Ruth Elena (Íkala, Revista de Lenguaje y Cultura, 2014)
In this article, the results of a research inquiring about representations that primary education English teachers from some public institutions in the city of Medellin, Colombia have about ideal of comprehensive education are presented. From a qualitative research approach, an open-ended question survey was implemented to 19 teachers and subsequently an in-depth interview was carried out to 5 teachers. Information collected was subject to the technique of critical discourse analysis by Teun Van Dijk (2003). The main findings revealed that these representations show five main thematic areas: (1) whole education for a multidimensional human being; (2) education of a valuable human being; (3) whole education, foreign language learning and different culture approaching; (4) whole education, foreign language teaching and autonomous people; (5) whole education and communicative competence in foreign language. It was found that teachers' representations about whole education have a marked ethic and moral, values and rules emphasis—and that it, being analyzed from foreign language teaching, must not be limited to basic linguistic structures usage in daily and immediate communication contexts.